Relationship between Vessel Formation and Seasonal Changes in Leaf Area of Evergreen and Deciduous Species with Different Vessel Arrangements - Sayaka Takahashi; Erina Takahashi (Plants, 2021)
To discuss the diversity of morphological traits and life strategies of trees, the functional relationship between leaf expansion and vessel formation must be clarified. We compared the temporal relationship among tree species with different leaf habits and vessel arrangements. Twigs, leaves, and trunk core samples were periodically acquired from 35 sample trees of nine species in a temperate forest in Japan. We quantitatively estimated leaf expansion using a nonlinear regression model and observed thin sections of twigs and trunks with a light microscope. Almost all of the first-formed vessels in twigs, which formed adjacent to the annual ring border, were lignified with a leaf area between 0% and 70% of the maximum in all species. The first-formed vessels in trunks lignified between 0% and 95% of the maximum leaf area in ring-porous deciduous Quercus serrata and ring-(radial-)porous evergreen Castanopsis cuspidate. Their lignification occurred earlier than in diffuse-porous deciduous Liquidambar styraciflua, diffuse-porous evergreen Cinnamomum camphora and Symplocos prunifolia, and radial-porous evergreen Quercus glauca and Quercus myrsinifolia. The timing varied in semi-ring-porous deciduous Acanthopanax sciadophylloides and diffuse-porous evergreen Ilex pedunculosa. The observed differences in the timing of vessel formation after leaf appearance were reflected in their differing vessel porosities and were connected to the different life strategies among tree species.